Hubungan lama pemakaian sepatu boots dengan angka kejadian tinea pedis pada pekerja pemungut Sampah dinas kebersihan daerah Kota surakarta - Fathin, M. Haidzar (2016)
Background: Tinea pedis is one of skin infections of the sidelines of the toes and the sole of foot caused by Trichophyton rubrum. Several researches reported that the often use of boots can have an important role in the incidence of Tinea pedis. Objective: This research aimed to analyze the correlation between the duration of wearing boots and incidence of Tinea pedis on the workers of garbage collector. Method: The research used observational method with design cross sectional research design. The number of sample was 57 respondents. The samples were the workers of garbage collector of Department of Cleanness of Surakarta. Purposive sampling was used in the method of sampling technique. The data were obtained from the interview and the examination of skin scraps. The statistical test was chi square. Results: The incidence of Tinea pedis in the workers of garbage collector was 33 respondents (57.9%) and those who did not suffer from Tinea pedis were 4 respondents (24.1%). From the result of the statistical chi square test, it was obtained the score of p = 0.004 (p < 0.05). Conclusion: There was a significant correlation between the duration of wearing boots and incidence of Tinea pedis.